Bahasa Arab dan Transformasi Peradaban Digital: Sebuah Perspektif Pendidikan Islam - Irfan Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The accelerating transformation of digital civilization places Arabic language education at an epistemological crossroads between the preservation of Islamic tradition and the demands of technological modernity. This study critically examines the position of Arabic language education within the framework of Islamic Education in responding to digital transformation, arguing that the dominant techno-optimist approach in current Arabic language learning obscures deeper epistemological and civilizational tensions. Employing a qualitative library research method, this study analyzes how the dichotomy between Arabic as a sacred linguistic heritage and Arabic as a communicative tool shapes pedagogical orientations in Islamic educational institutions. The analysis reveals three critical tensions: (1) the instrumentalization of Arabic language reduces its civilizational and spiritual dimensions; (2) the adoption of digital technology without adequate epistemological grounding risks creating a generation that masters Arabic tools but lacks deep comprehension of Islamic intellectual tradition; and (3) the centralization of digital infrastructure threatens the diversity of local Arabic language teaching traditions in Indonesia. This study proposes the concept of "Digital Civilizational Arabic Education" as an integrative framework that positions Arabic language not merely as a communication medium, but as a vehicle of Islamic civilization capable of engaging constructively with digital modernity. The implications of this study affirm the urgency of a critical and transformative curriculum reformation in Arabic language education within Indonesian Islamic educational institutions.